Analisis Pendekatan Objektif pada Cerpen “Aku dan Dia” Karya Putu Ayub - Fahira Adelina (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2025)
This research aims to analyze the short story "Aku and Dia" by Putu Ayub using an objective approach. The research method used by researchers is descriptive qualitative research. The data source used is the short story "Aku and Dia" by Putu Ayub in the short story collection "Me, He, and They". The data collection technique used in this research is the reading and note-taking technique. Based on the results of data analysis, intrinsic elements were found in the form of theme, point of view, plot/plot, setting, characters and characterization, language style and message.